AQUEOUS AND ALCOHOLIC PARSLEY (Petroselinum crispum) EXTRACTS SUPPLEMENTED INTO DRINKING WATER AND STOCKING DENSITY AFFECT PRODUCTIVE PERFORMANCE AND ANTIOXIDANT STATUS OF BROILERS - Ihab Mohammed Ali; Husam Hikmat Nafea; Ali Irfan ILBAS (Journal of Animal and Plant Sciences, 2025)
Present experiments were conducted to evaluate the effects of aqueous and alcoholic parsley (Petroselinum crispum) extracts supplemented into drinking water and stocking density on productive performance (body weight, body weight gain, feed consumption, feed conversion ratio, mortality rate, and production and economic index) and antioxidant status (malondialdehyde, glutathione and catalase) of broilers. Two different stocking densities (10 and 15 chickens / m2) and 5 different additive levels (0 - control treatment without additives; 4a - addition of 4 milliliters of aqueous extract per liter of water; 4c - addition of 4 milliliters of alcoholic extract per liter of water; 8a - addition of 8 milliliters of aqueous extract per liter of water; 8c - addition of 8 milliliters of alcoholic extract per liter of water) were evaluated. The study included 375 one-day old, unsexed ROSS 308 chicks, and were arranged as 2x5 factorial experiment (viz; factor 1 as two stocking densities and factor two as five additives). The chicks were randomly assigned to ten distinct treatment groups. Each treatment group was further divided into three replicates. Five treatment groups comprised ten chicks each (stocking density 10), while the remaining five groups contained fifteen chicks (stocking density 15). The results showed that treatment 8c was the best regarding weight gain, feed consumption, feed conversion ratio, reduced mortality rates, and production and economic index at both stocking densities. Treatment 4c also showed remarkable effectiveness but was lower than 8c for all studied traits. Based on the overall performance, treatments 4c and 8c are considered the best at a density of 10 chickens/m2. Present additive treatments reduced blood serum malondialdehyde, glutathione and catalase levels at both stocking densities, indicating a reduction in oxidative stress. In general, the density of 10 chickens was more effective in improving antioxidant indicators as compared to the density of 15 chickens.
Keywords: Aqueous and Alcoholic Extract; Parsley; Stocking Density; Antioxidant Traits; Broiler